1996
DOI: 10.1200/jco.1996.14.1.171
|View full text |Cite
|
Sign up to set email alerts
|

Relation between tumor size, quality of life, and survival in patients with colorectal liver metastases.

Abstract: QoL provides a better survival estimate than measurement of tumor size and could be used as a surrogate end point for survival in treatment trials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
68
0
3

Year Published

1998
1998
2016
2016

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 166 publications
(74 citation statements)
references
References 17 publications
3
68
0
3
Order By: Relevance
“…Rather, it is fully in line with the already consolidated evidence found in a number of other cancer populations [19]. Several studies have in fact shown that self-reported QoL frequently replaces important clinical data, such as performance status or tumor size, in final multivariate prognostic models [20,21].…”
Section: Editorialsupporting
confidence: 54%
“…Rather, it is fully in line with the already consolidated evidence found in a number of other cancer populations [19]. Several studies have in fact shown that self-reported QoL frequently replaces important clinical data, such as performance status or tumor size, in final multivariate prognostic models [20,21].…”
Section: Editorialsupporting
confidence: 54%
“…One explanation for the deterioration in the quality of life (QoL) of colorectal cancer patients (Earlam et al, 1996) is an immune response to tumour-related products. In support of this, QoL impairment in colorectal liver metastasis (CLM) patients has been shown to correlate more closely with extent of immune activation than with liver metastasis volume or the serum level of the tumour marker carcinoembryonic antigen (CEA) (Allen-Mersh et al, 1998).…”
mentioning
confidence: 99%
“…[1][2][3][4] More specifically, studies have suggested that such an association may exist among patients with advanced malignancies of the breast, 4 -10 esophagus, 11 colorectum, 2,12 skin (melanoma), 13,14 and lung. 2,[15][16][17][18][19][20] This trend also may occur among patients with terminal cancer 21 ; however, the magnitude and clinical relevance of these effects remain unclear.…”
mentioning
confidence: 99%